Fabrication of porous polymer particles containing BiVO4 and Fe3O4 nanoparticles using block copolymer as porogen for effective dye removal - Kraithep C. (2023)
Hybrid porous particles (HPPs) of poly(methyl methacrylate-divinylbenzene) P(MMA-DVB) containing a visible light-photocatalyst bismuth vanadate (BiVO4) and magnetite (Fe3O4) nanoparticles (NPs) were synthesized and employed as a reusable material for effective dye removal. The porous structure increasing the surface to volume ratio and high water diffusivity of HPPs, prepared via the microsuspension iodine transfer polymerization, was generated by using poly(methacrylic acid)-block-poly(MMA-3-[trimethoxysilyl] propyl methacrylate) (PMAA-b-P(MMA-MPS)) as porogen. The block copolymer also acting as a surface modifier of BiVO4 NPs allowed the encapsulation of this photocatalyst together with oleic acid coated Fe3O4 NPs in spherical HPPs. The fabricated HPPs could efficiently remove methylene blue (MB) up to 235 mg/g-BiVO4 based on the adsorption and photocatalytic degradation mechanism caused by the particle porosity and BiVO4 NPs, respectively. Moreover, the incorporated Fe3O4 NPs provided the magnetic separation ability of the HPPs for their reusability up to 5 cycles with a high MB removal performance of > 86. These HPPs would be good candidates for effective dye removal in contaminated water